Test–Retest Reliability of Cervical Strength Testing Protocols with Handheld Dynamometer in Prepubertal and Pubertal Untrained Boys - Christos Batatolis; Konstantina Karatrantou; Theodora Vasilopoulou; Konstantina Chanou; Nikolaos Tsiakaras; Vassilis Gerodimos (Journal of Functional Morphology and Kinesiology, 2025)
Background: The cervical spine plays an important role in several daily activities of children and adolescents, and thus, its evaluation using reliable protocols is of crucial importance. This study examined the test–retest reliability of cervical strength protocols using indices of absolute (standard error of measurement—SEM and 95% limits of agreement—LOA) and relative reliability (intraclass correlation coefficient—ICC). Methods: Twenty prepubertal (9.10 ± 0.61 years old) and twenty pubertal boys (13.6 ± 0.6 years old) participated in two assessment sessions separated by 48 h. During both sessions, maximal isometric strength (forward flexion, extension, and right–left lateral flexion) was assessed using a handheld dynamometer, and then, the cervical flexion-to-extension ratio (cervicalF/E ratio) was calculated. Results: According to our data analysis, good absolute and relative reliability was denoted for prepubertal boys in all cervical movements (ICC = 0.81–0.90; SEM% = 5.82–8.62); conversely, pubertal boys denoted high relative and absolute reliability in all directions of movements (ICC = 0.90–0.96; SEM% = 3.8–5.5). The cervicalF/E ratio showed moderate reliability in prepubertal (ICC = 0.71; SEM% = 9.11) and pubertal boys (ICC = 0.78; SEM% = 7). Conclusions: In conclusion, the isometric strength of cervical muscles, using a handheld dynamometer, showed acceptable reliability in prepubertal and pubertal boys; however, prepubertal boys demonstrated slightly lower reliability. Additionally, the assessment of the cervical F/E ratio should be interpreted with caution. However, it would be important to carry out future studies to strengthen the findings of the present study.